Debt Relief for Low-Income Countries and the HIPC Initiative - Thugge, Kamau (IMF Working Papers; Working Paper, 1997)
The paper describes the debt burden of low-income countries and the traditional mechanisms that have been implemented by the international community to alleviate this burden. While these mechanisms are sufficient to reduce the external debts of many heavily indebted poor countries (HIPCs) to sustainable levels provided these countries implement sound economic policies, they are likely insufficient for a number of countries. To deal with these cases, the World Bank and the IMF have jointly proposed and implemented the HIPC Initiative. The paper describes this Initiative and suggests that it should enable HIPCs to exit from the debt rescheduling process.